2016
DOI: 10.1111/jam.13125
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolium salts with antifungal potential for the control of head blight of wheat caused by Fusarium graminearum

Abstract: This study suggests the potential of using IMS as alternative to the hazardous standard fungicides in the management of Fusarium head blight of wheat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…In this study, we have chosen imidazolium ionic liquids with three different alkyl groups for determining (i) biofilm prevention and biofilm eradication activities on C. albicans strains and (ii) mode of action of promising ionic liquid on C. albicans cells. Although antifungal and antibiofilm activities of imidazolium ionic liquids have been studied previously (Bergamo et al, 2014Dalla Lana et al, 2015;Ribas et al, 2016), their effects on preformed C. albicans biofilms and their molecular toxicity mechanisms are largely unknown. This study provided a clear insight into the biofilm eradication potential of alkylimidazolium ionic liquids and mechanism of action of prospective antifungal ionic liquid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we have chosen imidazolium ionic liquids with three different alkyl groups for determining (i) biofilm prevention and biofilm eradication activities on C. albicans strains and (ii) mode of action of promising ionic liquid on C. albicans cells. Although antifungal and antibiofilm activities of imidazolium ionic liquids have been studied previously (Bergamo et al, 2014Dalla Lana et al, 2015;Ribas et al, 2016), their effects on preformed C. albicans biofilms and their molecular toxicity mechanisms are largely unknown. This study provided a clear insight into the biofilm eradication potential of alkylimidazolium ionic liquids and mechanism of action of prospective antifungal ionic liquid.…”
Section: Discussionmentioning
confidence: 99%
“…Activity of -hexadecyl side chain containing imidazolium ionic liquid against multidrug resistant Candida tropicalis and clinical dermatophyte strains showed potential activity against biofilms (Bergamo et al, 2014Dalla Lana et al, 2015). Inhibition of conidia germination and mycelial growth was observed in Fusarium graminearum (Ribas et al, 2016). Antifungal ionic liquids were incorporated into poly(L-lactide) biomaterials for inhibiting adhesion of Candida spp.…”
mentioning
confidence: 99%
“…; Ribas et al . ). They showed evidence to interfere in the ergosterol synthesis, one of the main sterols of the fungal cell membrane; however, the mechanism seems to be much more complex, and further investigations are necessary.…”
Section: Strategies To Combat Fungal Resistancementioning
confidence: 97%
“…Later, the same group examined the effect of the imidazolium salts on the phytopathogen F. gramineraum . 156 They observed that the antifungal activity was mostly modulated by that the counter ion. Another molecule containing long linear alkyl chains is phosphatidylethanolamine.…”
Section: New Antifungal Leadsmentioning
confidence: 99%